Critical assessment of wheat biofortification for iron and zinc: a comprehensive review of conceptualization, trends, approaches, bioavailability, health impact, and policy framework - Gupta, Om Prakash; Singh, Ajeet; Pandey, Vanita; Sendhil, Ramadas; Khan, Mohd. Kamran; Pandey, Anamika; Kumar, Sunil; Hamurcu, Mehmet; Ram, Sewa; Singh, Gyanendra (Frontiers in Nutrition, 2024)
Addressing global hidden hunger, particularly in women of childbearing age and children under five, presents a significant challenge, with a focus on iron (Fe) and zinc (Zn) deficiency. Wheat, a staple crop in the developing world, is crucial for addressing this issue through biofortification efforts. While extensive research has explored various approaches to enhance Fe and Zn content in wheat, there remains a scarcity of comprehensive data on their bioavailability and impact on human and animal health. This systematic review examines the latest trends in wheat biofortification approaches, assesses bioavailability, evaluates the effects of biofortified wheat on health outcomes in humans and animals, and analyzes global policy frameworks. Additionally, a meta-analysis of per capita daily Fe and Zn intake from average wheat consumption was conducted. Notably, breeding-based approaches have led to the release of 40 biofortified wheat varieties for commercial cultivation in India, Pakistan, Bangladesh, Mexico, Bolivia, and Nepal, but this progress has overlooked Africa, a particularly vulnerable continent. Despite these advancements, there is a critical need for large-scale systematic investigations into the nutritional impact of biofortified wheat, indicating a crucial area for future research. This article can serve as a valuable resource for multidisciplinary researchers engaged in wheat biofortification, aiding in the refinement of ongoing and future strategies to achieve the Sustainable Development Goal of eradicating hunger and malnutrition by 2030.